Editorial: Architecture as a Communicative Medium - Mathew, Anijo (Enquiry The ARCC Journal for Architectural Research, 2008)
Environmental psychology categorizes "physicalenvironment” as "typically neutral,” only coming into selfconscious awareness when individuals form stable andenduring representations of it [1]. We see this manifest inthe real world when the steeple of a church is able to communicate that it is a place for reflection and religious gathering; the bricks and ivy of Harvard Yard signifies years of scholarly research and education; the solid grey walls ofa prison conjures up images of torture and punishment; and the bright colors of a playground indicates play and joyfulness. In our relationship with architecture, we are ableto construct an understanding of our environment becausewe pick up such clues and cues from parts of ourenvironment and then construct a formulation of the whole based on our memories and knowledge. Thus, we are ableto communicate with the places we live in and the placeswe live in are able to act as interfaces for information interchange.